Leveraging IPFS for Scalable and Secure Data Storage in Blockchain-Based DApps - Richard Andre Sunarjo; Nanda Septiani; Dwi Nur Ramadha; Afif Aditya Darmawan; Omar Arif Al-kamari (APTISI Transactions on Management (ATM), 2026)
The rapid expansion of blockchain-based Decentralized Applications (DApps) has intensified challenges related to scalable, secure, and cost-efficient data storage, as conventional on-chain storage is unsuitable for large data volumes due to high gas costs and performance limitations, while centralized off-chain solutions undermine decentralization and increase security risks. This study aims to evaluate the effectiveness of integrating the IPFS as a decentralized storage layer within an Ethereum-based DApp architecture to enhance scalability, data integrity, and operational efficiency. Using an experimental systems engineering approach, a fully functional DApp prototype was developed by integrating a React.js frontend, Ethereum smart contracts written in Solidity, and a local IPFS node for off-chain file storage. Empirical performance testing was conducted to measure file upload and retrieval latency, CID (Content Identifier) consistency, smart contract execution time, and gas consumption on the Ethereum testnet. The results demonstrate that IPFS integration significantly reduces on-chain storage load while maintaining strong data integrity, as evidenced by 100% CID consistency across all test scenarios. Although upload and retrieval times increased proportionally with file size, the system achieved success rates above 95% with stable performance, while gas costs remained low because only CIDs were recorded on-chain. These findings indicate that IPFS provides a scalable, secure, and cost-efficient decentralized storage solution for blockchain-based DApps, enabling the development of more data-intensive and resilient DApps, with future research opportunities focusing on incentive-based pinning mechanisms, advanced encryption, and cross-chain storage integration.